Tulip in the Desert: A Selection of the Poetry of Muhammad Iqbal by Mustansir Mir. (Canada: McGill-Queen's University Press. 158 pages.) (American Journal of Islam and Society, 2001)
The poet-philosopher Muhammad Iqbal (1877-1938) of the Indiansubcontinent, who has been called the most serious Muslim philosophicalthinker of modem times by Fazlur Rahman, does not occupy the place hedeserves in the memory of the 'Umma of Islam today. For this fallen'Umma which has not produced world-class thinkers for centuries, this stateof amnesia cannot be afforded if the desire for revival is genuine. To thisend, I believe, the recent book of Mustansir Mir, Tulip in the Desert: ASelection of the Poetry of Muhammad Iqbal is a very timely contribution.The book consists of twelve short chapters preceded by an introductionon the life, poetry and philosophy of Iqbal. The author, who edited andtranslated this selection from Urdu and Farsi, is a professor in theDepartment of Philosophy and Religious Studies at Y oungston StateUniversity, Ohio. His book is more than a collection of Iqbal's poetry. Heputs his own background to the service of the reader. Each chapter startswith a commentary on the poems selected according to a theme. Each poemis supplied with extensive explanatory notes, which sometimes take morespace than the poem itself. As the author rightly states, these commentariesand notes elucidate Iqbal's use of historical, religious, philosophical andliterary resources of the Islamic tradition. The book is a comprehensiveintroduction to various aspects of Iqbal's ideology and art in his poetry.Considering that the number of existing books on Iqbal is far less thansufficient as compared to the magnitude and importance of his work, thepresent one is a significant contribution to commemorate Iqbal, and teachlay people, as well as the learned, his recipe for overcoming the problemsthat Muslims have been facing for centuries ...